Global university rankings : challenges for European higher education - Erkkilä, Tero (Palgrave Macmillan, 2020)
Global University Rankings explores the novel topic of global university rankings and their effects on higher education in Europe. The contributions in this volume outline different discourses on global university rankings and explore the related changes concerning European higher education policies, disciplinary traditions and higher education institutions. The first global university rankings were published less than a decade ago, but these policy instruments have become highly influential in shaping the approaches and institutional realities of higher education. The rankings have portrayed European academic institutions in a varying light. There is intense reflexivity over the figures, leading to ideational changes and institutional adaptation that take surprisingly similar forms in different European countries. The contributions in this book critically assess global university rankings as a policy discourse that would seem to be instrumental to higher education reform throughout Europe